Impact of salt reduction in meals consumed during hemodialysis sessions on interdialytic weight gain and hemodynamic stability. Issue 4 (6th April 2018) - Colson, Arthur; Brinkley, Anita; Braconnier, Philippe; Ammor, Nadia; Burnier, Michel; Pruijm, Menno
Abstract: Introduction: Patients on hemodialysis (HD) are advised to limit daily water‐ and salt intake to reduce interdialytic weight gain (IDWG). To counterbalance protein‐losses, protein‐rich meals are sometimes provided during HD sessions, but their salt content is not always taken into account. The aim of this study was to assess the influence of a lower salt content of meals provided during HD sessions on IDWG, blood pressure (BP), and hemodynamic stability during dialysis. Methods: This monocentric, interventional study was proposed to all the patients treated with three weekly HD sessions. The first two months of the study (high salt period), the patients continued to receive one sandwich containing 2.4 g of salt per session. Then, we reduced its salt content from 2.4 to 1.4 g, and patients received this "low‐salt sandwich" at each dialysis session for four months. The mean values of IDWG, BP, and dry weight of the first two months were compared with those collected during the low salt periods (2–6 months). Findings: Forty out of 76 patients who initially agreed to participate were free of hospitalization, transplantation, and transfer to another center or death during the study period and were included in the final analysis (35% women). Median age was 63 years (range 28–90), 22.5% had a residual diuresis > 0.5 L/day. IDWG baseline decreased from 2.17 ± 0.98 to 2.03 ± 1 kg (P = 0.001) two months and to 2.09 ± 1.01 kg (P = 0.009) four months after we had lowered the salt content of the sandwich. The number of symptomatic intradialytic hypotension was also reduced (6.1% vs., respectively, 3.2% and 3.3% of HD sessions; P = 0.004). Discussion: IDWG was reduced and hemodynamic stability improved after the reduction of the salt content of perdialytic meals. This suggests that salt consumed during HD matters and might influence salt and water intake outside the dialysis unit.